Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1634/theoncologist.2013-0457
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Signs of Impending Death in Cancer Patients

Abstract: Background. The physical signs of impending death have not been well characterized in cancer patients. A better understanding of these signs may improve the ability of clinicians to diagnose impending death. We examined the frequency and onset of 10 bedside physical signs and their diagnostic performance for impending death. Methods. We systematically documented 10 physical signs every 12 hours from admission to death or discharge in 357 consecutive patients with advanced cancer admitted to two acute palliativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
200
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 152 publications
(211 citation statements)
references
References 34 publications
5
200
1
3
Order By: Relevance
“…At the end of life, swallowing problems can be as high as 79 %, and these difficulties may not only result in discomfort for patients but also can raise concern for caregivers [4]. Dysphagia of liquids, decreased level of consciousness, and poor performance status appeared at high frequency with a positive likelihood ratio for impending death [22]. Similarly, dysphagia had prognostic significance for 1-2-week survival [23,24].…”
Section: Dysphagiamentioning
confidence: 99%
“…At the end of life, swallowing problems can be as high as 79 %, and these difficulties may not only result in discomfort for patients but also can raise concern for caregivers [4]. Dysphagia of liquids, decreased level of consciousness, and poor performance status appeared at high frequency with a positive likelihood ratio for impending death [22]. Similarly, dysphagia had prognostic significance for 1-2-week survival [23,24].…”
Section: Dysphagiamentioning
confidence: 99%
“…Claessens et al and Hui et al reveal that most patients tend to experience varying levels of consciousness as part of the natural dying process, which tends to occur 7-10 days prior to death. (25,26) This point is important given that Kohara et al (27) and Mercadante et al (28) both showed that CSD tends to be applied 2-3.4 days before death, suggesting that most patients would already be experiencing varying levels of sedation and cognitive impairment before CSD is applied. (25)(26)(27)(28) 5.…”
Section: The Practical Triumviratementioning
confidence: 99%
“…(25,26) This point is important given that Kohara et al (27) and Mercadante et al (28) both showed that CSD tends to be applied 2-3.4 days before death, suggesting that most patients would already be experiencing varying levels of sedation and cognitive impairment before CSD is applied. (25)(26)(27)(28) 5. Variations in level of consciousness to sedation: Lipuma's key argument is that CSD results in the negation of higher brain function, which he believes is integral to a meaningful existence.…”
Section: The Practical Triumviratementioning
confidence: 99%
“…Recent research suggests that physical signs such as pulselessness of the radial artery, respiration with mandibular movement, decreased urine output, Cheyne-Stokes breathing, and death rattle are more associated with a high likelihood of death within 3 days. 4 Sitting during the medical visit 5 and examining the patient 6 are perceived by patients as highly positive and compassionate aspects of care and will help alleviate some of the distress associated with uncertainty.…”
Section: What Can We Do In the Meantime?mentioning
confidence: 99%